CO2, 13C/12C AND H2O VARIABILITY IN NATURAL BASALTIC GLASSES: A STUDY COMPARING STEPPED HEATING AND FTIR SPECTROSCOPIC TECHNIQUES - AN INFRARED SPECTROSCOPIC STUDY - Macpherson C.G.; Hilton D.R.; Newman S.; Mattey D.P. (My University, 1999)
A comparison of two independent techniques was used to assess the homogeneity of CO2 and H2O concentrations in a number of natural basaltic glasses. Variations in carbon concentration and isotopic ratio were determined by comparison of stepped heating data obtained in two different laboratories. Dissolved volatile concentrations were also obtained by stepped heating and Fourier Transform Infrared (FTIR) spectroscopy. Replicate stepped heating analyses of a mid-ocean ridge basaltic glass show that the concentration and 13C/12C of bulk magmatic and dissolved CO2 vary by less than +/-10% and +/-0.5%%, respectively. A similar degree of correlation is observed for replicate stepped heating analyses of Mariana Trough glasses conducted in two different laboratories. Dissolved CO2 concentrations determined by stepped heating also correlate well with concentrations measured by FTIR spectroscopy. The correspondence of results obtained in these experiments provide an upper limit to the degree of natural variation in concentrations and isotopic ratios of these volatiles in basaltic glasses and suggest that intrinsic, magmatic carbon has a relatively homogeneous distribution in these glasses. Water concentrations determined through extraction by heating and FTIR also show excellent agreement.